2021
DOI: 10.3390/su13084181
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Economic Complexity in Switzerland and Its Contribution to Inclusive and Sustainable Change

Abstract: The UN Sustainable Development Goals (SDGs) aim at harnessing economic complexity for sustainable and inclusive economic growth by calling for a decade of joint action. In this paper, we show how the action-oriented collaborative culture of complex and competitive economic ecosystems in places outside the major population centers may generate significant positive external effects for society and the environment at large. We illustrate this by means of two small case studies in Switzerland, a country with a fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(46 reference statements)
1
3
0
1
Order By: Relevance
“…This study extends previous sustainable development research by clarifying the potential causal linkages among sustainable development, external and internal business environments. The research results of this study go beyond corroborating with prior empirical studies that suggest various dimensions of the external and internal business environment evolvement according to the sustainable development goals fulfillment (Aerni, 2021; Camilleri, 2020; Nasiri et al, 2022; Ren & Jackson, 2020). In this study, sustainable development was found to positively cause changes in freedoms of movement for labor, capital, and goods, an absolute absence of coercion or constraint of economic liberty.…”
Section: Discussion and Theoretical Contributionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study extends previous sustainable development research by clarifying the potential causal linkages among sustainable development, external and internal business environments. The research results of this study go beyond corroborating with prior empirical studies that suggest various dimensions of the external and internal business environment evolvement according to the sustainable development goals fulfillment (Aerni, 2021; Camilleri, 2020; Nasiri et al, 2022; Ren & Jackson, 2020). In this study, sustainable development was found to positively cause changes in freedoms of movement for labor, capital, and goods, an absolute absence of coercion or constraint of economic liberty.…”
Section: Discussion and Theoretical Contributionsupporting
confidence: 87%
“…Issues of sustainable, self-sufficient economic agents' development that do not deplete natural resources have gained increasing popularity and taken into account by policymakers worldwide. This implies (Aerni, 2021;Camilleri, 2020;Nasiri et al, 2022;Ren & Jackson, 2020). In this study, sustainable development was found to positively cause changes in freedoms of movement for labor, capital, and goods, an absolute absence of coercion or constraint of economic liberty.…”
Section: Discussion and Theoretical Contributionmentioning
confidence: 60%
“…104 Switzerland's growing ECX can also have a positive impact on its global competitiveness and environmental performance. 105 Thus, ECX can help transform both countries’ economies in an environmentalist direction. Contrary to the findings of Neagu and Teodoru, 21 Neagu, 57 and Rafique et al, 26 our results are in line with those of Dogan et al, 55 who suggest that ECX has a positive effect on the environment in Germany and Switzerland.…”
Section: Discussionmentioning
confidence: 99%
“…According to Aerni [50], the United Nations Sustainable Development Goals (SDGs) can harness economic complexity to explore potential pathways toward sustainable and inclusive economic growth. Furthermore, in accordance with Cakir et al [51], countries that achieve high levels of economic complexity (meaning a high level of diversity in productive capabilities and a low level of ubiquity products that reflect a kind of sophistication) in a holistic manner are well equipped to respond to external shocks through internal processes that can also impact their future export structure and sustainability (in terms of resilience).…”
Section: Dimensions Of Sustainabilitymentioning
confidence: 99%